Gate-induced enhancement of spin-orbit coupling in dilute fluorinated graphene - Guzman Arellano, Robert Mikhail (2015)
We analyze the origin of spin-orbit coupling (SOC) in fluorinated graphene using Density Functional Theory (DFT) and a tight-binding model for the relevant orbitals. As it turns out, the dominant source of SOC is the atomic spin-orbit of fluorine adatoms and not the impurity induced SOC based on the distortion of the graphene plane as in hydrogenated graphene. More interestingly, our DFT calculations show that SOC is strongly affected by both the type and concentrations of the graphene's carriers, being enhanced by electron doping and reduced by hole doping. This effect is due to the charge transfer to the fluorine adatom and the consequent change in the fluorine-carbon bonding. Our simple tight-binding model, that includes the SOC of the 2p orbitals of F and effective parameters based on maximally localized Wannier functions, is able to account for the effect. The strong enhancement of the SOC induced by graphene doping opens the possibility to tune the spin relaxation in this material.